Stress modulation of hafnium-based ferroelectric material orientation in 3D cylindrical capacitor - Wenqi Li; Zhiliang Xia; Meiying Liu; Yong Cheng; Bao Zhang; Yuancheng Yang; Lei Liu; Zongliang Huo (AIP Advances)
Hafnium-based ferroelectric materials have attracted a lot of attention, but the distributions of the materials need to be tuned for commercialization, including phase distribution and polarization orientation distribution. The orientation of ferroelectric materials plays a significant role in memory device performance; however, there have been no reliable methods to control this orientation until now. This paper investigates the control of ferroelectric phase polarization orientation in 3D cylindrical capacitors. This optimization is made possible because the 3D cylindrical capacitor allows stress application in the tangential, axial, and radial directions, offering a wider range of adjustment options than 2D planar structures. The study focuses on how stress distribution affects ferroelectric phase orientation in hafnium-based materials when the diameters of cylindrical capacitors are varied. First, stress simulations are conducted to analyze the stress distribution in cylindrical capacitors with different diameters. The results indicate that the hafnium oxide layer experiences increased radical stress as the capacitor diameter decreases. Subsequently, capacitors with two different diameters are fabricated, significantly improving the polarization orientation in the thinner one. It is found that the capacitor diameter and the polarization orientation are strongly related through the correlation analysis. Finally, we demonstrate the improvement in the polarization orientation of ferroelectric thin films by radical stress through first-principles calculations. This study provides valuable insights into how stress distribution influences polarization orientation in hafnium-based ferroelectric films and is crucial for advancing the use of ferroelectric materials in future technologies.